2016
DOI: 10.1021/acs.chemmater.6b01731
|View full text |Cite
|
Sign up to set email alerts
|

Block Copolymer with an Extremely High Block-to-Block Interaction for a Significant Reduction of Line-Edge Fluctuations in Self-Assembled Patterns

Abstract: Directed self-assembly (DSA) of block copolymers (BCPs) with a high Flory−Huggins interaction parameter (χ) provides advantages of pattern size reduction below 10 nm and improved pattern quality. Despite theoretical predictions, however, the questions of whether BCPs with a much higher χ than conventional high-χ BCPs can further improve the line edge roughness (LER) and how to overcome their extremely slow self-assembly kinetics remain unanswered. Here, we report the synthesis and assembly of poly-(4vinylpyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 59 publications
0
28
1
Order By: Relevance
“…Accurate characterization of the interfacial width is important for lithographic materials as it is potentially a limiting factor in the performance of a BCP as an etch mask. 51 Polystyrene- b -poly(methyl methacrylate) (PS- b -PMMA) is the most commonly explored material for lithographic applications, but it suffers from a number of limitations. Recent results have shown that while the material will form regular patterns down to L 0 ≅ 18 nm, the pattern will not effectively transfer to the underlying substrate at that length scale.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate characterization of the interfacial width is important for lithographic materials as it is potentially a limiting factor in the performance of a BCP as an etch mask. 51 Polystyrene- b -poly(methyl methacrylate) (PS- b -PMMA) is the most commonly explored material for lithographic applications, but it suffers from a number of limitations. Recent results have shown that while the material will form regular patterns down to L 0 ≅ 18 nm, the pattern will not effectively transfer to the underlying substrate at that length scale.…”
Section: Introductionmentioning
confidence: 99%
“…124–128 More recently, structuralizing nanomaterials based on a template have been actively researched to make precisely arranged structure with high throughput and cost effectiveness. A template is utilized to guide the material to the predefined form of the template to make nanomaterial structures with high resolution over a large area by applying simple processes, such as deposition or synthesis 5,64–76. In addition, the template‐based method is easy to combine with a transfer method, enabling the structuralization of nanomaterials on flexible and stretchable substrates 129,130.…”
Section: Fabrication Of Geometrically Structured Nanomaterialsmentioning
confidence: 99%
“…In addition, the template‐based method is easy to combine with a transfer method, enabling the structuralization of nanomaterials on flexible and stretchable substrates 129,130. A method to use BCP is an efficient technique to make various nanostructures, such as cylindrical, lamellar, and spherical morphologies, by self‐assembly based on chemically different interaction of two bonded BCPs on a prepatterned template substrate 64,65,67,69,70. The pattern size, shape, and density can be adjusted by variation of the composition and weight of the BCP, and tens of nanoscale patterns can also be produced 131,132.…”
Section: Fabrication Of Geometrically Structured Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, PS‐ b ‐PDMS has been widely investigated for DSA application due to its high χ and high content of Si. [17a,b,21] Also, to overcome slow interdiffusion issue of high‐χ BCPs, various techniques such as warm solvent annealing,[17f,22] warm spin casting,[17e] flash light annealing, and microwave annealing were employed.…”
Section: Introductionmentioning
confidence: 99%